2008
DOI: 10.2118/103344-pa
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Acidizing: What Role Does Formation Softening Play in Production Response?

Abstract: Summary Fracture acidizing of carbonates has yielded increases in production in many areas of the world, but depending on rock strength and reservoir closure pressure, this response may be lower than expected. Also, as a result of rock strength and closure pressure, production may decline at a higher rate than following a proppant fracture treatment. Laboratory results are presented describing the effect of various acid systems on the strength reduction of limestone -nd dolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…It can also reduce fracture initiation pressure. This conclusion supports the results of previous studies [17][18][19]. In field fracturing operation, if steering acid is injected directly into the wellbore, it will quickly react with carbonate rocks in the formation.…”
Section: Discussionsupporting
confidence: 91%
“…It can also reduce fracture initiation pressure. This conclusion supports the results of previous studies [17][18][19]. In field fracturing operation, if steering acid is injected directly into the wellbore, it will quickly react with carbonate rocks in the formation.…”
Section: Discussionsupporting
confidence: 91%
“…Some empirical correlations were based on experiments (Nierode and Kruk 1973;Nasr-El-Din et al 2008;Pournik 2008), and some correlations were developed theoretically (Gangi 1978;Walsh 1981;Swan 1983;Gong et al 1999). Some empirical correlations were based on experiments (Nierode and Kruk 1973;Nasr-El-Din et al 2008;Pournik 2008), and some correlations were developed theoretically (Gangi 1978;Walsh 1981;Swan 1983;Gong et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Nasr-El-Din et al 15 suggested modifying the Nierode and Kruk correlation, which had been lumped together, without taking into account the lithology. Through individual evaluations of data, by lithology, they recalculated the correndersonsonnndnlation constants, resulting in a more precise and differentiated set of correlations 15,16 . 3.…”
Section: Figurementioning
confidence: 99%